The Effect of Perceived Usefulness and Perceived Risk to the Utilization of Internet Banking (Study on BRI Internet Banking Customers in Semarang City) - Fahmi, Tubagus; Wiratama, Bayu (Universitas Negeri Semarang, 2018)
This study aims to analyze the effect of perceived usefulness and perceived risk of consumers to internet banking utilization. The population of this study is the bank’s customers who use BRI’s internet banking in semarang city with the number of samples are 50 respondents by using purposive sampling technique. The result of this study shows that the significance value of simultaneous hypothesis test < 0.05, thus Ho is rejected. It means that Ho stating both perceived usefulness and perceived risk variable significantly affect to the participation of BRI bank members in Semarang city is accepted. In addition, the partial hypothesis of t-test for the perceived usefulness variable is 5.949 with the significance value < 0.05, thus Ho is rejected. The test result of perceived risk variable obtained t count value equal to 3.925 with the significance value < 0.05, then Ho is rejected. It means that the performance of hypothesis (H1) stating the perceived usefulness and perceived risk variable significantly influence to the success of BRI bank in Semarang city is accepted. The conclusion of this study is that the higher perceived usefulness and perceived risk to the consumer will enhance the success of internet banking utilization. The recommendation for the future research is that they should consider other variables which have effect to the internet banking utilization.